Library Setting In Improving Literacy In Learning In Palur State Primary School 01 - Putri, Intan Dwi Kartika; Fatoni, Achmad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The library is the relevant work unit of the school, apart from that the library is the most important source to support improving the quality of education in schools. This research aims to 1) Describe the spatial layout implemented in the SD Negeri Palur 01 library to improve learning literacy. 2) Describe the obstacles and efforts faced by library space planning in improving learning literacy at SD Negeri Palur 01. In this research, qualitative descriptive research methods were used, including interview, observation and documentation methods. The data in this research comes from interviews with students, class teachers and librarians starting in July 2023, observing the library room and documenting the library room. Research results with data validity using triangulation of sources and techniques. With an interactive model, analysis techniques, namely data reduction, data presentation and drawing conclusions, are: 1) The library and librarian at SDN Palur 01 already exist but the arrangement is not neat, for example the bookshelves are not neatly arranged and the placement of items is still messy. 2) Librarians and teachers have worked together to invite students to visit the library and familiarize themselves with literacy in learning at SDN Palur 01.